PERCERAIAN KARENA FAKTOR EKONOMI DI DESA SUNGAI NYIRIH KECAMATAN SELAKAU KABUPATEN SAMBAS - Nuryanti, Melly; Marluwi, Marluwi; Hakimah, Nur (Al-Usroh, 2023)
This article examines divorce due to economic factors in Desa Sungai Nyirih, Kecamatan Selakau, Kabupaten Sambas. The purposes of this research were to find out: 1) Indicators of factors that cause divorce in Desa Sungai Nyirih, Kecamatan Selakau, Kabupaten Sambas; 2) The view of Islamic law on divorce due to economic factors in Desa Sungai Nyirih, Kecamatan Selakau, Kabupaten Sambas. This study used qualitative methods as the type of research used to obtain the data, the data sources used in this study were: 1) primary data sources data obtained from interviews with residents who experienced divorce due to economic factors; 2) secondary symbiotic data from books, journals and KHI (Islamic Law Compilation). This study also uses data collection guidelines using observations and interviews and uses data collection tools with interviews and smartphones to document images and sound recordings via cell phones. Based on this analysis, the researcher concluded that: 1) economic factors were one of the effects of divorce because there was no inner livelihood and love lost because of the husband's selfishness in providing a living, there was no level because it was by the husband's ability to meet the needs of life. 2) the view of Islamic law in the Shiqot Taklik Talak, if the husband does not provide for 3 months in a row divorce or the wife demands a divorce from her husband, divorce is allowed if there are problems experienced between the spouses.